Searching for faces in crowd chokepoint videos. Issue 2 (15th December 2019) - Kramer, Robin S. S.; Hardy, Sarah C.; Ritchie, Kay L.
Summary: Investigations of face identification have typically focussed on matching faces to photographic IDs. Few researchers have considered the task of searching for a face in a crowd. In Experiment 1, we created the Chokepoint Search Test to simulate real‐time search for a target. Performance on this test was poor (39% accuracy) and showed moderate associations with tests of face matching and memory. In addition, trial‐level confidence predicted accuracy, and for those participants who were previously familiar with one or more targets, higher familiarity was associated with increased accuracy. In Experiment 2, we found improvements in performance on the test when three recent images of the target, but not three social media images, were displayed during searches. Taken together, our results highlight the difficulties inherent in real‐time searching for faces, with important implications for those security personnel who carry out this task on a daily basis.